Transformative Processes in Environmental Education: A Case Study - Helen Fox; Tally Palmer; Rob O'Donoghue (Environmental Association of Southern Africa, 2016)
This paper presents a case study on the severely degraded Boksburg Lake's (Gauteng, South Africa) social-ecological system, and on an environmental-education initiative that aimed to support the lake's transformation with a view to its improved social and ecological well-being. In this case study, three key characteristics of the initiative which appeared to support the transformative process are discussed, namely: 1. Learning was aligned with the local social-ecological context; 2. Human-to-human and human-to-ecological connections were encouraged; and 3. The youth played a key role in initiating and effecting transformation. Apparent consequences of this particular environmental-education approach include: local people becoming involved and invested in an environmental-education process that was highly meaningful to them; a deeper connection being nurtured among participating stakeholders, as well as between the youth and Boksburg Lake; a collective identity being adopted to bring about change; knowledge of Boksburg Lake's social- ecological system being strengthened; acknowledgement of personal culpability in the lake's degradation; many of the youths changing their negative environmental practices; and local stakeholders, including the youth, engaging in collective action to reclaim Boksburg Lake. Furthermore, a range of new practices emerged from the Schools for a Sustainable Environment (SSE) initiative. The literature is drawn on to explain the possible consequences of this initiative. Through this paper, it is hoped that environmentaleducation practitioners will be provided with useful conceptual tools to support their work.